Rancang Bangun Jaringan Komputer Local Area Network Pada PT.Mars Material Mitraindo - Jesslin Halim; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
At present, PT.Mars Material Mitraindo only uses 2 computers to operate. This makes PT.Mars Material Mitraindo employees have to take turns in using a computer to input financial data. This queue makes employee performance inefficient in terms of time. So PT.Mars Material Mitraindo plans to add 14 units of computers to streamline employee performance. The method used in this research is to analyze in making simulations and designing systems. The first step taken in this study is to analyse of the placement of each computer unit then makes a simulation of it to packet tracer. The second step is to test each computer unit to make sure each computer is connected to each other. The results achieved in this study are an increase in data efficiency by 79.5978% and time efficiency by 78.1835% of the amount of data downloaded by the type of document data. Key words: internet, LAN, data exchange